An examination of hand preferences, reaction times and some power parameters of athletes in short track and curling branches - Gursoy, R.; Sadr, Y.; Ozan, M. (BMJ Open Sport & Exercise Medicine, 2017)
The aim of this study is to define hand choice, reaction time and measurement of some parameters of male and female national athletes competing in short track and curling branches. With collected findings it is aimed to define the differences between the genders and make a contribution since very limited scientific studies are available about these branches in Turkey. Total of 24 of 10 female national athletes with average age of "16.70" and 14 male national athletes with average age of "16.64". Competing in short track and curling branches were participated to this study. Within the study, Oldfield Edinburg handedness inventory was used for defining athletes` hand choice and simple reaction test of Davis and Frank is used for measuring reaction time. For the consideration of gained data descriptive statistics is used and independent samples t test is used on 0.05 importance level. According to findings collected from the participants, there is a significant difference in genders in terms of height, leg power, right hand and left hand grip power on 0.05 importance level on behalf of male athletes. There is not a significant difference between male athletes` branches and average values of measured parameters according to 0.05 importance level. According to variances between branches, values of leg power of male athletes in curling branch are higher than male athletes in other branches. It is found out that average of height, leg power, right hand and left hand grip power of male athletes are higher than female athletes. However, there is not a significant difference between two groups in terms of average values of reaction time and hand choice variances.